Functionalization process of coking sludge: Biochar immobilizing with Fe/Co to enhance the wastewater treatment of ozone. (February 2023) - Pan, Jiamin; Pang, Zijun; Wei, Tuo; Ke, Xiong; Wei, Cong; Cheng, Xiaoqian; Qin, Zhi; Hu, Yun; Wei, Chaohai; Li, Fusheng
Abstract: In order to make full use and resourcefulness of the products produced in the coking wastewater treatment process, solve the residual problem of wastewater, and achieve clean production, a sludge-derived metal catalyst was prepared in this paper using metal-doped coking sludge. The catalyst has a regulated lattice surface ordering, surface exposure of metal oxides, pore size exposure and functional chemical bonding, which enhances the catalytic activity of ozone (O3 ). The catalytic performance of the catalyst was tested in refractory wastewater where the catalyst modified its biodegradability, chemical oxygen demand (COD) removal efficiency and humic acid structure. Compared to the catalytic treatment with biochar alone, the removal efficiency of total organic carbon (TOC), COD and ultraviolet absorption (UV254 ) were significantly increased by 35.67 %, 57.23 % and 45.44 %. Various energy conversions and valence transitions of Fe and Co metals within the catalyst catalyzed the generation of hydroxyl radicals (OH), superoxide radical (O2 - ) and singlet oxygen ( 1 O2 ) from O3 . In this study, high value-added functional catalysts were synthesized from biochar with Fe/Co and organic skeleton structure, which was prepared from coking sludge. The degradation of pollution in biological treatment of coking wastewater (BTCW) was performed and the mechanism was elucidated. The environmental risk in wastewater treatment process was controlled by "disposal wase with waste" approach, which has important practical application value. Graphical abstract: Unlabelled Image Highlights: Coking sludge-derived Fe/Co-biochar functionalized catalysts were synthesized. Fe/Co-biochar has superior magnetic separation performance and stability. TOC removal rate was in accordance with the secondary reaction kinetic model. The activation of O3 to generates reactive oxygen species as OH, O2 − and 1 O2 . Achieved the reduction of hazardous wastes and "disposal wase with waste".